A rare heterozygous TREM2 coding variant identified in familial clustering of dementia affects an intrinsically disordered protein region and function of TREM2. Issue 1 (15th September 2019) - Karsak, Meliha; Glebov, Konstantin; Scheffold, Marina; Bajaj, Thomas; Kawalia, Amit; Karaca, Ilker; Rading, Sebastian; Kornhuber, Johannes; Peters, Oliver; Diez‐Fairen, Monica; Frölich, Lutz; Hüll, Michael; et al.
Abstract: Rare coding variants in the triggering receptor expressed on myeloid cells‐2 ( TREM2 ) gene have been associated with Alzheimer disease (AD) and homozygous TREM2 loss‐of‐function variants have been reported in families with monogenic frontotemporal‐like dementia with/without bone abnormalities. In a whole‐exome sequencing study of a family with probable AD‐type dementia without pathogenic variants in known autosomal dominant dementia disease genes and negative for the apolipoprotein E ( APOE) ε4 allele, we identified an extremely rare TREM2 coding variant, that is, a glycine‐to‐tryptophan substitution at amino acid position 145 (NM_018965.3:c.433G>T/p.[Gly145Trp]). This alteration is found in only 1 of 251, 150 control alleles in gnomAD. It was present in both severely affected as well as in another putatively affected and one 61 years old as yet unaffected family member suggesting incomplete penetrance and/or a variable age of onset. Gly145 maps to an intrinsically disordered region (IDR) of TREM2 between the immunoglobulin‐like and transmembrane domain. Subsequent cellular studies showed that the variant led to IDR shortening and structural changes of the mutant protein resulting in an impairment of cellular responses upon receptor activation. Our results, suggest that a p.(Gly145Trp)‐induced structural disturbance and functional impairment of TREM2 may contribute to the pathogenesis of an AD‐like form of dementia.